The Effect of Simple Drawing Stimulation on Hand-Eye Coordination in 7-8 Years Children with Mental Retardation in Banyumas Regency - Azizah, Anhar Nur; Azizah, Ulfa (Proceedings Series on Health & Medical Sciences, 2024)
Background : The development of hand-eye coordination in children with mental retardation duffers from that of typically developing children. Stimulation is needed to enhance the development of hand-eye coordination. Objective : To prove the effect of simple drawing stimulation on hand-eye coordination in children with mental retardation aged 7-8 years in Banyumas regency. Methods : This quantitative research used a quasi-eksperimental designs with a non-equivalent control group. The respondents in study were children with mental retardation aged 7-8 years in Banyumas regency. The sample cosisted of 32 children, with 16 children in experiment group and 16 in control group, selected using the total sampling technique. Results : Most children with mental retardation had Down Syndrome, accounting for 13 (41%) out of 32 children. Based on the level of mental retardation, mild mental retardation was the most common, with 20 (63%) out of 32 children. Most children were 7 years old, totaling 19 (59%) and the majority were male, with 22 (69%). The results of this study show a significant effect of simple drawing stimulation on hand-eye coordination os indicated by paired sample t-test for both experimental group (0,005) and the control group (0,001) (p ? 0.005). The independent sampel test also yielded a significant value (0,121) (p ? 0,005). Conclusion : Simple drawing stimulation affects the development of hand-eye coordination with a significant value 0,001 (p ? 0.005).